Experimental investigations of utilizing cellulosic biomass for biofuel productions on multi-platforms - Yang, Yang (Kansas State University, 2023)
Biofuels derived from cellulosic biomass offer one of the best near- to mid-term alternatives to fossil fuels. Consuming bioenergy instead of fossil fuels can reduce greenhouse gas emission and benefit to the nation’s energy security. The conversion can be done either on biochemical platform or thermochemical platform. Cellulosic bioethanol is developed as an alternative to petroleum-based liquid fuel on the biochemical platform. It can be used on its own as a sustainable liquid transportation fuel or blended with conventional transportation fuel. On thermochemical platform, combustion is proven to efficiently utilize biomass for heat and power generation by co-firing with coal. To efficient convert cellulosic biomass into biofuels, biomass need to go through size reduction for bioethanol conversion. Particle size is critically important to energy consumption in its preprocessing and the efficiency in bioconversion. In the application of co-firing, the resulting fuel quality after biomass densification is also crucial to make biomass a cost effective solid fuel. This research provide fundamental knowledges and insights in biofuel manufacturing on biochemical and thermochemical platforms. A guidance on the effect of particle size through the whole bioethanol conversion process is provided. An investigation on solid fuel upgrading effects from synchronized torrefaction and pelleting (STP) system is also performed. At last, a preliminary study of a pathway on integrating these two platforms of cellulosic biomass utilization is performed. This half thesis consists of 8 chapters. Firstly, an introduction of this research is given in Chapter 1.Secondly, Chapter 2 provides a literature review on cellulosic bioethanol conversion process. Chapter 3and 4 present a comprehensive study on effect of particle size in both biomass pre-processing and bio-conversion. Chapter 5 reviews application of biomass on thermochemical platform. Chapter 6 studies the fuel upgrading effect from using STP system. A preliminary study on integrating two platforms of cellulosic biomass utilizations is presented in Chapter 7. Finally, conclusions are presented in Chapter 8.
Keywords: Bioethanol; Pretreatment; Particle size; Solid fuel; Pelleting; Torrefaction